Ligth ions and ozone - generaion and interactions with living organisms - Kříha, V.; Aubrecht, L. (Вопросы атомной науки и техники, 2005)
With directly in the living organism born ions exception, LNI coming through three phases: ionisation, attachment by the electronegative molecules and the clusters formation due to local electrostatic interactions. The quantitative analysis of physical parameters leads to conclusion that we cannot find any physical property (till known) explaining the positive affect of LNI on living organisms. Analysis of possible mechanism produces several hypotheses of LNI-organism interaction. A simplified semi-quantitative model of respiratory tract was developed for estimation of ions and ozone interaction with living organisms. A formation of oxygen radicals and products of their chain-reactions in intrinsic conditions is discussed.